A STUDY ON CONTRASTIVE PARALLEL-STRUCTURED SENTENCES UNDER SEMANTIC FIELD PERSPECTIVE - Nguyen Van Thao (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2020)
Contrastive parallel-structured sentence (CPSS) was a traditionally artistic kind of Vietnamese literature, which was originated from the Chinese. The aims of this article is to investigate all kinds of the CPSS and the semantic field aspects inherently existing in it; adding that the article targets in what social occasions the Vietnamese use the CPSS the most. To have a deep insight into the semantic field aspects in the CPSS, the article has applied integrated methods such as descriptive method, analytical method and statistic method. In this article, the semantic field in the CPSS was showed, analyzed and discussed to reveal the application of linguistic units such as the phenomena of synonyms, antonyms, homonyms, fixed phrases and especially semantic field, adding that to show how words are exploited with the same semantic field.